Phytochemicals and Biological Activity of Desert Date (Balanites aegyptiaca (L.) Delile) - Hosakatte Niranjana Murthy; Guggalada Govardhana Yadav; Yaser Hassan Dewir; Abdullah Ibrahim (Plants, 2020)
Many underutilized tree species are good sources of food, fodder and possible therapeutic agents. Balanites aegyptiaca (L.) Delile belongs to the Zygophyllaceae family and is popularly known as “desert date”, reflecting its edible fruits. This tree grows naturally in Africa, the Middle East and the Indian subcontinent. Local inhabitants use fruits, leaves, roots, stem and root bark of the species for the treatment of various ailments. Several research studies demonstrate that extracts and phytochemicals isolated from desert date display antioxidant, anticancer, antidiabetic, anti-inflammatory, antimicrobial, hepatoprotective and molluscicidal activities. Mesocarp of fruits, seeds, leaves, stem and root bark are rich sources of saponins. These tissues are also rich in phenolic acids, flavonoids, coumarins, alkaloids and polysterols. Some constituents show antioxidant, anticancer and antidiabetic properties. The objective of this review is to summarize studies on diverse bioactive compounds and the beneficial properties of B. aegyptiaca.